P058 Two cases of deliberate antiretroviral overdose: raltegravir and tenofovir disaproxil fumarate/emtricitabine. (30th June 2016) - Wainwright, Emma; Tang, Alan; Chen, Fabian
Abstract : Background/introduction: There is a high incidence of psychiatric illness amongst those living with HIV. This is associated with a risk of deliberate self harm including overdose with antiretrovirals. There are a small number of publications describing overdose with antiretrovirals but none describing overdose with raltegravir. Aim(s)/objectives: In this report we aim to describe two cases of overdose with antiretrovirals: the management, investigations and resultant complications. Methods: The patient case notes and laboratory test results were reviewed. Results: Case 1: A 28 year old HIV-positive man presented 96 hours after taking a deliberate overdose of 40 x 400mg raltegravir tablets. He developed mild symptoms of diarrhoea, abdominal cramps and a sore chest. Results post-overdose: electrolytes and renal function: normal; liver function tests: ALT 58, others normal; creatinine kinase 67; haematology: normal; therapeutic drug monitoring (TDM) results: raltegravir not detected 96 hours post overdose. There were no serious complications. Case 2: A 52 year old HIV-positive man presented 24 hours after taking a deliberate overdose of 18 × Truvada (tenofovir disaproxil fumarate/emtricitabine). He had no symptoms related to the overdose. Results post-overdose: urinalysis: normal; electrolytes and renal: phosphate 0.75, creatinine 94; TDM: 24 hours: 207 ng/ml; 48 hours: 80 ng/ml; 72 hours: 16 ng/ml; 192 hours: 2 ng/ml. There were no serious complications. Discussion/conclusion: The patients in our case series showed few side effects and no serious sequelae as a result of their overdose. There seems to be little guidance available to guide management of such cases.